Campus Eirunepé do Instituto Federal de Educação, Ciência e Tecnologia do Amazonas: investigação narrativa de sujeitos que contam uma trajetória histórica - Sousa, Renan Rocha de Holanda (2020)
This research comes from the Professional Master's Program of the Graduate Program in Professional and Technological Education (ProfEPT), offered by the Federal Institute of Education, Science and Technology of Amazon State (IFAM). We had as general objective to elaborate the historical trajectory of the IFAM Campus in the municipality of Eirunepé, countryside of Amazon state, through the narrative investigation provided by the interaction between the researchers and four historical subjects interviewed. The research has a qualitative character and its typology is phenomenological, of an interpretative nature. We have the historical narrative as a theoretical reference. As a methodology for data analysis, we list the narrative investigation. The semi-structured interview complemented by documentary research is configured as a data collection methodology. We made up an educational product to this dissertation, an ebook that covers the history of Professional and Technological Education (EPT) in Brazil and Amazon state, historical and socioeconomic characteristics of the municipality of Eirunepé/AM and the institution's historical trajectory. We explored the discussions through a metaphor, the historical route as a process of “forestation”, where the interviewed subjects, which we started to call “Seed”, “Butterfly”, “Metamorphosis” and “Tree”, were an integral part. Our research object remains open and other routes can be taken to investigate it. This research recorded the institution's history through the analysis of a history seen from below. In addition, it reflected the importance of defending and strengthening of IFAM/Campus Eirunepé and the institutions that are part of the Federal Network of Professional, Scientific and Technological Education (RFEPCT).